Multifunctionalized polyurethane–polyurea nanoparticles: hydrophobically driven self-stratification at the o/w interface modulates encapsulation stability1. Issue 38 (14th October 2015) - Rocas, Pau; Fernández, Yolanda; Schwartz, Simó; Abasolo, Ibane; Rocas, Josep; Albericio, Fernando
<x xml:space="preserve">Abstract</x> The combination of an amphiphilic and a hydrophobic reactive prepolymer promotes the self-stratification of the whole PUUa NP by hydrophobic interactions.